Fabrication of copper sulfide using a Cu-based metal organic framework for the colorimetric determination and the efficient removal of Hg2+ in aqueous solutions. (28th September 2015) - Xiong, Yuhao; Su, Linjing; Yang, Haiguan; Zhang, Peng; Ye, Fanggui
Abstract : From a Cu-based metal organic framework to copper sulfide by wet-treatment: towards the colorimetric determination and the efficient removal of Hg 2+ . Abstract : CuS (PCuS) particles were facilely synthesized by the wet-treatment of a Cu-based metal organic framework (HKUST-1). PCuS possesses an impressive intrinsic peroxidase-like activity. As a result of this affinity, PCuS readily binds to 3, 3′, 5′, 5-tetramethylbenzidine (TMB) in the presence of hydrogen peroxide (H2 O2 ) ( K m values of 29 μM and 150 μM toward TMB and H2 O2, respectively). Interestingly, when Hg 2+ was added, HgS produced in conjunction with the specific binding sites on the surface of PCuS remarkably inhibited the peroxidase-like activity of PCuS. Based on this unique property, a sensing platform for the colorimetric detection of Hg 2+ was established. In addition, high surface area and strong affinity for Hg 2+ make PCuS an excellent adsorbent for Hg 2+ (2105 mg g −1 ). These results indicate that PCuS could be a useful material for the facile detection and the efficient removal of Hg 2+ using HKUST-1 as a precursor in environmental abatement applications.